Reconstructing 1200 years of Hydroclimate Variability in the Southern Margins of the Arabian Desert: Insights From a Paleo-Lake in Southern Yemen - Parth, Shah; Russell, James; Waldmann, Nicolas (Frontiers in Earth Science, 2021)
The climate of the Arabian Desert is not well documented during the past two millennia due to the scarcity of continuous and well-dated terrestrial archives in the region. Reliable interpretation from the climatic records from this region are pivotal for identifying periodicities of inter-annual to multi-decadal variability and trends driven by shifts in position of the Intertropical Convergence Zone (ITCZ) and the strength of the monsoons. A high-resolution multiproxy approach is presented for a ~3.3 m composite core, GBW, from a karst lake located in Ghayl ba Wazir, southern Yemen. Sedimentary proxies, including particle size distribution, coupled with magnetic susceptibility (MS) and geochemistry (XRF), provide a comprehensive picture of sediment depositional changes that may be linked to climate and environmental variability over the southern Arabian Desert. The chronology of the GBW core is provided by five radiocarbon (14C) dates from terrestrial macrofossils (wood and twigs) extracted from sediment samples and indicates the core extends to ~900 CE. Our data indicates generally wetter conditions from 930-1400 CE corresponding to the 'Medieval climate anomaly (MCA)' followed by arid phases during 1410-1700 CE coinciding with the 'Little Ice Age (LIA)'. Evidence for a drier LIA include high authigenic calcium precipitation (Ca/ (Al + Fe + Ti)), decreased TOC/TIC values, and gypsum precipitation, whereas the wetter MCA is characterized by higher detrital element ratios (Ti/Al, K/Al, Rb/Sr), and increased TOC/TIC and deposition of finer sediments (EM1). Furthermore, end-member mixing analyses (EMMA) derived from the grain-size distribution (EM2 and EM3) corroborates the deposition of coarser silt sediment through wind erosion and production of carbonate sand during the LIA concurrently with low lake levels under generally dry conditions. Aridity during the LIA is consistent with evidence and theory for weakened boreal summer monsoons during intervals of northern hemisphere cooling.